TOURISM IN UZBEKISTAN AS A FACTOR OF INTERCULTURAL COMMUNICATION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines the main factors influencing the current state and development of cultural tourism in Uzbekistan. The author's division of the factors of cultural tourism development into groups is presented from the perspective of the market and state mechanism with the allocation of criteria.